The modeling of the thermohydrodynamic regime of Ivankovskoye reservoir - G A Saminsky (RUDN Journal of Engineering Research, 2014)
Numerical three-dimensional modeling of Ivankovskoye reservoir allows to estimate the influence of thermal inflow of the electric power station Konakovskaya. The model have been used for studying a thermic structure of the reservoir upon extremely hot meteorological conditions.